The Responsibility of the Teacher in Improving Creative Abilities (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This scientific article notes that the dramaturgy of musical theater is important. We will also discuss the progress we have made in this regard and the challenges that need to be addressed in the future. The importance of this topic lies in the fact that the history of our statehood, our rich past and culture, the spirituality of our great ancestors are fully expressed through modern theatrical art.